Determinants of open educational resources adoption and their impact on educational sustainability: A cross-cultural comparison using SEM-fsQCA - Alkawsi G.; Al-Sharafi M.A.; AlAjmi Q. (Springer, 2025)
This cross-cultural study investigates the factors influencing the adoption of open educational resources (OER) and their impact on educational sustainability in Malaysia and Oman. The research extends the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model by incorporating four additional constructs: design, perceived interactivity, ethics, and PT. A quantitative research methodology was employed, involving a survey of 380 educators. Partial least squares structural equation modeling (PLS-SEM) and fuzzy-set qualitative comparative analysis (fsQCA) were used to analyze the data. The findings reveal that effort expectancy, design, ethics, and PT are crucial in influencing OER adoption behavior in Malaysia. The most influential factors in Oman are design, PINT, and PT. Additionally, the study confirms the positive impact of OER adoption on educational sustainability in both countries. These results offer valuable insights for policymakers, educators, and institutions seeking to promote and implement OER effectively, emphasizing the importance of ethical considerations, user-friendly design, and trust-building measures in fostering OER adoption and contributing to sustainable educational practices. ? The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.